2011
DOI: 10.1108/02640471111156786
|View full text |Cite
|
Sign up to set email alerts
|

Batch loading in metadata creation: a case study

Abstract: This is the author's manuscript for a work which, at the time of deposit to RUcore, was under formal review managed by a socially recognized publishing entity. The manuscript may or may not have been subsequently published. Content and layout follow publisher's submission requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Other findings indicated that the metadata director is required to cooperation with professionals and accurately organize and transmit information. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Other findings indicated that the metadata director is required to cooperation with professionals and accurately organize and transmit information. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%